Advances and Challenges in Oral Biofilm Control - Panariello, Beatriz Helena Dias [UNESP]; de Araújo Costa, Cecilia Atem Gonçalves; Pavarina, Ana Cláudia [UNESP]; Santiago, Sérgio Lima; Duarte, Simone [UNESP] (Springer Nature, 2017)
Purpose of Review: The paper aims to critically study the literature published over the past 3 years as relevant to oral biofilm control. The emphasis of this review is the interests and importance of new findings, seeking the following answers: (i) what is the major challenge in oral biofilm control?, (ii) what are the new anti-biofilm approaches?, and (iii) what are the further researches? Recent Findings: In addition to mechanical plaque removal and the use of chemical agents against pathogenic biofilm, there is a need for development of new anti-biofilm approaches. The majority of the new studies aiming to control oral biofilm have been performed with the characterization of the extracellular matrix components. Exopolysaccharides (EPS), proteins, lipids, nucleic acids (eDNA), lipoteichoic acids (LTA), and lipopolysaccharides have been identified in the matrices of bacterial biofilms and are considered the current targets to oral biofilm control. Summary: The extracellular matrix is essential for the existence of the biofilm and by its virulence both in bacterial and fungal pathogens. The better understanding of the biomechanical properties of the EPS matrix is the main advance and is leading to new chemical and/or biological approaches to remove or disorganize cariogenic biofilms. Recently, researches are focusing on the extracellular matrix for oral biofilm control with further clinical applicability.
Keywords: Biofilm control; Dental caries; Extracellular matrix; Oral biofilms; Oral fungi; Oral microbiota